How effective is allopurinol at suppressing recurrent gout attacks?. Issue 9 (September 2016) - Cook, Jennifer; Maly, Annika; Palmer, Jaime; Bailey, Justin
Abstract : Evidence‐Based Answer : Allopurinol does not appear to reduce the number of gout attacks compared with placebo, febuxostat, or benzbromarone, in patients with gout; however, allopurinol is effective at lowering serum urate (SOR: B, meta‐analysis of lower quality RCTs).